Integration of fiscal policy and accountability to improve public services in Indonesia: From transfers to outcomes - Isman, Muhammad Herdyan Sukmana; Salomo, Roy Valiant; Bakri, Muhammad Rafi (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2025)
Fiscal transfers are critical tools for supporting local service delivery and reducing regional disparities in Indonesia’s decentralized governance system. Their effectiveness, however, depends on the capacity of local governments to manage and utilize these funds responsibly. This study aims to analyze the impact of fiscal transfers on public service performance, with a particular focus on the moderating role of governance accountability. Utilizing panel data of 2,540 observations from 2019 to 2023, the analysis applies a random effects regression model to evaluate the effect of general allocation funds (DAU), special allocation funds (DAK), and revenue-sharing funds (DBH) on the Public Service Index. Governance accountability is measured through the Government Agency Performance Accountability System (SAKIP) and the Government Internal Supervisory Apparatus (APIP), which are incorporated as moderating variables. The results show that fiscal transfers significantly improve public service outcomes, but their impact is substantially greater in regions with high SAKIP and APIP scores, indicating that fiscal resources alone are insufficient to enhance services without effective institutional accountability. The study contributes to fiscal federalism theory and offers practical insights for policymakers. Its novelty lies in integrating fiscal capacity and governance accountability within a single empirical framework to explain decentralized service performance.